1999
DOI: 10.1093/tropej/45.1.14
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of individual, household, and environmental risk factors for intestinal helminth infection among children in Qena Governorate, Upper Egypt

Abstract: During 1994 a cross-sectional survey was carried out on a sample representative of the population in Qena Governorate, Upper Egypt, to investigate the relationship between intestinal helminthic infection among children and a wide range of variables (demographic, behavioural, cultural, socioeconomic, and environmental). Data were collected by direct observation and by administering a questionnaire to mothers in charge of the household in a sample of 768 households representative of the entire population in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
4
18
2
2
Order By: Relevance
“…This condition probably reflects, on the one hand, the poverty level of the indigenous population studied, and on the other, problems in communication between these people and the health services: many indigenous people have difficulty in speaking Spanish, and doctors at health centers do not speak the indigenous language predominant in the region (almost 100% of doctors working in health services in Chiapas speak no indigenous language). Both situations affect access to health services Although it has been reported that ascariosis shows convex prevalence and intensity patterns with age, 27,43,44 in our study no significant association was found between age and the presence of ascariosis. Two plausible explanations for this fact can be advanced: firstly, it has been reported that Ascaris lumbricoides is more prevalent in children than adults, but its physiopathology is not associated with an individual's predisposition related to age in terms of growth; secondly, overcrowding among the population under study could affect this association (in the present study overcrowding was at the borderline of statistical significance).…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…This condition probably reflects, on the one hand, the poverty level of the indigenous population studied, and on the other, problems in communication between these people and the health services: many indigenous people have difficulty in speaking Spanish, and doctors at health centers do not speak the indigenous language predominant in the region (almost 100% of doctors working in health services in Chiapas speak no indigenous language). Both situations affect access to health services Although it has been reported that ascariosis shows convex prevalence and intensity patterns with age, 27,43,44 in our study no significant association was found between age and the presence of ascariosis. Two plausible explanations for this fact can be advanced: firstly, it has been reported that Ascaris lumbricoides is more prevalent in children than adults, but its physiopathology is not associated with an individual's predisposition related to age in terms of growth; secondly, overcrowding among the population under study could affect this association (in the present study overcrowding was at the borderline of statistical significance).…”
Section: Discussioncontrasting
confidence: 71%
“…In many studies, water contamination was associated with high intestinal parasitic infection. 27,33 The variable maternal education level 33 has been found to be significantly associated with parasitosis in other studies; however, in our survey it was not significant, there were not enough data (information was obtained from about 377 mothers) or most of the mothers from whom information was collected had very low education levels (< three years formal education).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…2 Another study from Egypt observed that children living in villages near a river or desert, considered to have low levels of services such as sewage, garbage disposal and water supply, were at greater risk of infection than town residents. 18 Another study from Vietnam also concluded that intestinal parasites spread through poor hygienic practices, evidenced by contaminated finger nails and unclean hands. 19 This study has several strengths.…”
Section: Discussionmentioning
confidence: 99%